2020
DOI: 10.15376/biores.15.2.2163-2170
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical analysis of bamboo and agro-industrial residue one-layer particleboard

Abstract: A high-density particleboard composed of peanut shells (Arachis hypogaea L.), an agro-industrial residue, and bamboo wastes of the species Dendrocalamus giganteus (branches and apical part), bonded with a two-component polyurethane resin based on castor oil (Ricinus communis L.) in the proportion of 12% of the particleboard mass, was produced. Four types of specimens were prepared according to the percentage of peanut shells: 0%, 10%, 20%, and 30%. Mechanical characteristics were evaluated through the flexural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Similar trends were reported in the literature as Guler et al (2008) and Nasser et al (2020). Guler et al (2008) found that increasing the percentage of peanut hulls in the composition of the panels significantly decreased the mechanical properties.…”
Section: Mechanicals Properties Of Medium Density Particleboardssupporting
confidence: 87%
See 3 more Smart Citations
“…Similar trends were reported in the literature as Guler et al (2008) and Nasser et al (2020). Guler et al (2008) found that increasing the percentage of peanut hulls in the composition of the panels significantly decreased the mechanical properties.…”
Section: Mechanicals Properties Of Medium Density Particleboardssupporting
confidence: 87%
“…The values obtained for the MOR ranged between 9.90 and 15.54 MPa and for the MOE the values found were between 1,276.76 and 2,145.71 MPa. Nasser et al (2020) observed that the increment of peanut hulls in the composition of the panels was also responsible for a reduction in the strength of MOR and MOE. For the MOR the composition of the panels with 100% bamboo particles showed the highest value and the composition with higher content of peanut hulls evidenced the lowest value.…”
Section: Mechanicals Properties Of Medium Density Particleboardsmentioning
confidence: 94%
See 2 more Smart Citations
“…Brito et al (2020a) concluded that bamboo can be used as an alternative material for the manufacture of particleboard for indoor uses. Nasser et al (2020) verified panels made of bamboo and peanut shells met the parameters established by Brazilian Standard -NBR 14.810-2 (2013), Brazilian Association of Technical Standards -ABNT (2013) and American National Standards Institute -ANSI A208-1 (1999).…”
Section: Introductionmentioning
confidence: 79%